Cyber-Based Integrative Learning Design In Pesantren: A Systematic Literature Review On Islamic Education Transformation - Iro Waziroh; Imam Fuadi; Nur Kholis; Kandiri Kandiri; Zohaib Hassan Sain (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
The rapid development of digital technology has created significant challenges and opportunities for Islamic boarding schools (pesantren) in maintaining their educational identity while adapting to the demands of the digital era. This condition necessitates innovative learning transformations that integrate Islamic values with technological advancements through sociological approaches that consider social, cultural, and educational dynamics within pesantren communities. Therefore, this study aims to analyze the application of sociological approaches in transforming pesantren learning through digital platforms and to identify their implications for students’ academic and character development. This research employs a Systematic Literature Review (SLR) to examine and synthesize relevant scholarly publications on digital learning transformation, sociological perspectives in education, and pesantren development. The collected literature was analyzed thematically to identify key patterns, challenges, and outcomes associated with the implementation of cyber-based integrative learning models. The findings reveal that integrating digital platforms into pesantren education significantly enhances students’ technological competencies, learning effectiveness, academic performance, and access to broader knowledge resources. Furthermore, students demonstrate greater openness toward contemporary scientific knowledge while maintaining strong adherence to Islamic teachings and values. The interaction among students, educators, and digital technology fosters collaborative learning environments, strengthens social awareness, improves adaptability to educational changes, and supports the development of critical thinking skills. The study implies that the transformation of pesantren education through a sociological and cyber-based integrative approach not only contributes to academic advancement but also reinforces students’ Islamic identity, character formation, and social responsibility. These findings provide strategic insights for policymakers, pesantren leaders, and educators in designing sustainable digital learning systems that are both technologically adaptive and grounded in Islamic values.